Realism and fear in international relations Morgenthau, Waltz and Mearsheimer reconsidered - Pashakhanlou, Arash Heydarian (Palgrave Macmillan, 2017)
This book examines the fascinating story of how the chief architects of realism (Hans Morgenthau, Kenneth Waltz and John Mearsheimer) dealt with some of the most pressing political issues of our time through the lenses of fear. Pashakhanlou conducts the most comprehensive evaluation of their works to date, compromising of a meticulous analysis of 400 of their publications